2019
DOI: 10.1093/nsr/nwz041
|View full text |Cite
|
Sign up to set email alerts
|

Rock-salt and helix structures of silver iodides under ambient conditions

Abstract: Many different phase structures have been discovered for silver iodides. The β and γ phases were found to be the most common ones at ambient conditions, while the rock-salt phase was found to be stable under pressures between 400 MPa and 11.3 GPa. Recently, the α phase was demonstrated to be stable under ambient conditions when the particle sizes were reduced to below 10 nm. However, no other phase has been reported to be stable for silver iodides under ambient conditions. Rock-salt and helix structures have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Carbon nanotubes have been demonstrated to act as effective templates and nanoreactors to synthesize and stabilize particular meta-stable nanostructures. [14][15][16][17][18][19][20][21][22][23][24] Here, we postulate a previously unknown square columnar phosphorus structures (SC-P) and compare their stability to that of nanoribbons. SC-P structures form inside single-walled carbon nanotubes (SWCNTs) with inner diameter around 1.0 nm, whereas zigzag nanoribbons of phosphorus (ZR-Ps) have been observed to form inside wider multi-walled carbon nanotubes (MWCNTs) with inner diameter of 4.1 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes have been demonstrated to act as effective templates and nanoreactors to synthesize and stabilize particular meta-stable nanostructures. [14][15][16][17][18][19][20][21][22][23][24] Here, we postulate a previously unknown square columnar phosphorus structures (SC-P) and compare their stability to that of nanoribbons. SC-P structures form inside single-walled carbon nanotubes (SWCNTs) with inner diameter around 1.0 nm, whereas zigzag nanoribbons of phosphorus (ZR-Ps) have been observed to form inside wider multi-walled carbon nanotubes (MWCNTs) with inner diameter of 4.1 nm.…”
mentioning
confidence: 99%
“…Adding to this problem, selective synthesis of specific phosphorus allotropes, especially on the nanoscale, remains a formidable challenge. Carbon nanotubes have been demonstrated to act as effective templates and nanoreactors to synthesize and stabilize particular metastable nanostructures. …”
mentioning
confidence: 99%
“…found a helix structure of AgI encapsulated inside SWCNTs with small diameters (~1.4 nm), which is different from those encapsulated inside MWCNTs with larger diameters (4—8 nm) (Figure 18b). [ 232 ] Recently, Zhang et al . reported that a new phase of square columnar of zigzag phosphorus nanoribbons preferably formed in CNTs with inner diameter around 1.0 nm, whereas black phosphorus nanoribbons formed in CNTs with a 4.1 nm inner diameter.…”
Section: Controlled Synthesis Of One‐dimensional Hybrids With the Template Of Carbon Nanotubesmentioning
confidence: 99%
“… High-resolution transmission electron microscopy (HRTEM) images (a–c), molecular dynamics simulation (d, e) and radial distribution calculation results (f) of silver iodides inside MWCNTs [ 2 ]. …”
mentioning
confidence: 99%
“…In an article published in National Science Review [ 2 ], Zhang's group from Xi’an Jiaotong University developed a method to stabilize the metastable structures to ambient conditions by utilizing the inner narrow space of carbon nanotubes, inspired by the size effect on the phase transition of silver iodide [ 3 ] and the special inner physical and chemical environments of carbon nanotubes [ 2 ]. In the inner space of carbon nanotubes, high-pressure conditions were sustained for the material reactions.…”
mentioning
confidence: 99%